The Use of Mind Mapping Technique to Improve the EFL Students’ Reading Comprehension Ability of Darussalam Polytechnic - M. Bambang Purwanto; Marsinah Marsinah (Universitas PGRI Palembang, 2021)
Mind maps are visual frameworks such as figures, diagrams, or charts used to present structural knowledge spatially with the intention of empowering comprehension and learning. Mind maps are effective in terms of helping communicate information because they can clarify complex concepts into simple, meaningful displays so that learners can develop a holistic understanding of the content to be learnt. Teachers may use mind mapping technique at different stages of instruction for example during instruction to prepare students to approach new information and clarify complex ideas, or after instruction to assess and reinforce learning and instruction. This article reports on an investigation into the use of mind mapping technique whether it can improve reading comprehension ability and the students’ opinions towards the use of mind mapping technique. The research design used in this study was one-group pre test-post test design. The study employed both quantitative and qualitative data analyses from pre-and post-tests, a questionnaire, and an interview. The participants of the study were 35 first-year students enrolling in a compulsory reading course called Communication and Reading Skills at Darussalam Polytechnic of Palembang. Fifteen students (5 highly successful, 5 who did not show any improvement, and 5 unsuccessful) were selected for retrospective interviews. The results suggested that 1) The English reading comprehension post test mean score of students was higher than the pre test mean score at the 0.05 level of significance; 2) most students were satisfied with their own reading comprehension ability; 3) they enjoyed working in group and agreed that mind mapping technique was a useful technique and can be applied to non- English subjects. Findings and implications for further research are discussion.